Informational Practices of the Medical Staff in University Hospital Centers: Crossroads of the Scientific Logic and the Professional Culture - Balicco, Laurence; Bertier, Marc; Clavier, Viviane; Mounier, Evelyne; Paganelli, Céline; Staii, Adrian (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
The digital technologies produce important changes in the specialized information practices. This study aims at characterizing the practices of the medical staff in university hospitals. This population is particularly interesting since the informational practices are both a support for the professional activities and a means of continuous formation. Les technologies numériques modifient les pratiques de l’information spécialisée. Cette étude cherche à caractériser les pratiques des médecins hospitaliers face à l’affluence des ressources numériques. Cette population est particulièrement intéressante car les démarches informationnelles représentent à la fois une activité support de la pratique professionnelle et un moyen de formation continue.